Subcutaneous pseudomycetoma of the knee caused by Acremonium species in a diabetic male: A case report - Viplov V. Vaidya; Sagar Chandrakar; Nitin S. Kumbhar; Kailash M. Jorule; Kumar Raushan; Nikhil S. Sane; Sohini Arora (Journal of Family Medicine and Primary Care)
A subcutaneous infection in the form of pseudomycetoma is rare. Acremonium species are rarely considered to be pathogenic in subcutaneous infections due to their ubiquitous nature. We report a case of subcutaneous pseudomycetoma over the dorsolateral aspect of the left knee caused by Acremonium species in a 55-year-old diabetic male who was treated successfully with oral itraconazole.